SYNTHESIS AND CHARACTERIZATION OF MONTMORILLONITE/TiO2 COMPOSITES AS A PHOTOCATALYST IN REDUCING BOD AND COD OF DOMESTIC WASTEWATER - Hayati, Ismi; Bawa Putra, Anak Agung; Sutha Negara, I Made (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
The development of hotels in Bali is increasing every year, this is directly proportional to the number of tourists and the waste generated. Hotel liquid waste has the potential to pollute the environment if there is no pre-disposal treatment. This study aims to obtain the best MMT/TiO2 composite that acts as an adsorbent and photocatalytic in reducing BOD (Biological Oxygen Demand) and COD (Chemical Oxygen Demand) levels of domestic wastewater. Composite synthesis was carried out by combining the top-down method, ball milling, and sonication. The ball milling method is used to produce montmorillonite, which has a smaller size, with a ball mass to sample mass ratio of 2:1 at a speed of 250 rpm. Variations in milling times of 0, 2, 4, and 6 hours were applied to determine the effect of milling time. The sonication method was used to obtain a smaller TiO2 particle size by exposing it to ultrasonic waves for 30 minutes. Calsination of the composite was carried out at a temperature of 400 Â°C. The results of composite characterization using the PSA (Particle Size Analyzer) showed that the composite did not meet the nanoparticle requirements because it had a particle size > 100 nm with a PI value > 0.5, which was still classified as polydispersity. NMT 6 has the best PI value of 0.65, which is then used to determine the optimum composite time to reduce BOD and COD levels. The optimum irradiation time obtained from composites in degrading waste is 90 minutes, which can reduce BOD levels by 78.53% and COD levels by 69%. The ability of composites NMT-6 to reduce BOD and COD levels is greater than that of montmorillonite and TiO2.